Taxes and the financial structure of German inward FDI - Fred Ramb; Alfons J. Weichenrieder (Deutsche Bundesbank, 2005)
The paper analyses the financial structure of German inward FDI. From a tax perspective, intra-company loans granted by the parent should be all the more strongly preferred over equity the lower the tax rate of the parent and the higher the tax rate of the German affiliate. From our study of a panel of more than 8,000 non-financial affiliates in Germany, we find only small effects of the tax rate of the foreign parent. However, our empirical results show that subsidiaries that on average are profitable react more strongly to changes in the German corporate tax rate than this is the case for less profitable firms. This gives support to the frequent concern that high German taxes are partly responsible for the high levels of intra-company loans. Taxation, however, does not fully explain the high levels of intra-company borrowing. Roughly 60% of the cross-border intra-company loans turn out to be held by firms that are running losses.
Keywords: H25; F23; 330; foreign direct investment; financial structure; taxation; Direktinvestition; Internationale Finanzierung; Kapitalstruktur; Auslandsniederlassung; Steuerbelastung; Deutschland